Unaltered Glutamate Transporter-1 Protein Levels in Aquaporin-4 Knockout Mice. (January 2017) - Hubbard, Jacqueline A.; Binder, Devin K.
Maintenance of glutamate and water homeostasis in the brain is crucial to healthy brain activity. Astrocytic glutamate transporter-1 (GLT1) and aquaporin-4 (AQP4) are the main regulators of extracellular glutamate and osmolarity, respectively. Several studies have reported colocalization of GLT1 and AQP4, but the existence of a physical interaction between the two has not been well studied. Therefore, we used coimmunoprecipitation to determine whether a strong interaction exists between these two important molecules in mice on both a CD1 and C57BL/6 background. Furthermore, we used Western blot and immunohistochemistry to examine GLT1 levels in AQP4 knockout (AQP4 −/− ) mice. An AQP4-GLT1 precipitate was not detected, suggesting the lack of a strong physical interaction between AQP4 and GLT1. In addition, GLT1 protein levels remained unaltered in tissue from CD1 and C57BL/6 AQP4 −/− mice. Finally, immunohistochemical analysis revealed that AQP4 and GLT1 do colocalize, but only in a region-specific manner. Taken together, these findings suggest that AQP4 and GLT1 do not have a strong physical interaction between them and are, instead, differentially regulated.